2012
DOI: 10.2172/1047928
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the U.S. Department of Energy's Home Energy Scoring Tool

Abstract: NOTICEThis report was prepared as an account of work sponsored by an agency of the United States government. Neither the United States government nor any agency thereof, nor any of their employees, makes any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Reference herein to any specific commercial produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Changes to the Home Energy Score methodology since the pilot version have adjusted the model's energy calculations. For results using more recent versions of the Home Energy Score see Roberts et al 2012. For documentation of the changes made to the Home Energy Score see or the Home Energy Score documentation (LBNL 2010).…”
Section: Energy Modeling Resultsmentioning
confidence: 99%
“…Changes to the Home Energy Score methodology since the pilot version have adjusted the model's energy calculations. For results using more recent versions of the Home Energy Score see Roberts et al 2012. For documentation of the changes made to the Home Energy Score see or the Home Energy Score documentation (LBNL 2010).…”
Section: Energy Modeling Resultsmentioning
confidence: 99%
“…A 2008 pilot study [4] found 190 Home Energy Saver, REM/Rate, and SIMPLE residen-tial simulation models had a 25.1-96.6% error rate compared with actual monthly electrical energy usage. A 2012 study [5] found that 859 residential models across Home Energy Saver, REM/Rate, and SIMPLE had a mean absolute percentage difference of 24% compared with actual monthly electrical energy use and of 24-37% compared with actual natural gas use for a sample size of 500 houses. All of these studies use comparisons with monthly utility bill data; the challenge of accurately matching hourly or 15-minute data for dozens of sub-metered data channels is significantly more difficult.…”
Section: Simulation Accuracymentioning
confidence: 99%
“…Their usefulness is dramatically greater for existing buildings, for which existing data can be used to calibrate the energy model. However, differences between models and actual monthly utility bills on the order of 24-97% [4,5] are common. Many measurement and verification (M&V) protocols specify a required accuracy for a model to be legally useful; almost all organizations use ASHRAE Guideline 14 (subsection 5.3.2.4.f) which specifies a coefficient of variance for root mean squared error, RMSE, of <15% or 30% and a normalized mean bias error, NMBE, of <5% or 10% for calibrating to monthly or hourly data, respectively [6].…”
Section: Introductionmentioning
confidence: 99%
“…For results using more recent versions of the Home Energy Score see Roberts et al 2012. For documentation of the changes made to the Home Energy Score see or the Home Energy Score documentation (LBNL 2010).…”
Section: Figure 18 Home Energy Score Gas Demand Versus Wall Insulationmentioning
confidence: 99%